Die Ausgrabung in Höhle 1 von Ava Ranga Uka A Toroke Hau - Moser, Johannes (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
The German Archaeological Institute in cooperation with their Rapa Nui counterpart carried out several surveys and excavations at Ava Ranka Uka A Toroke Hau in the Quebrada Vaipu. The archaeo-logical investigation in the Cave 1 yielded clear evidences for the use of this site as a temporary shelter or refuge since pre-colonial times. Features in the form of several stone structures and a great quantity of lithic remains was unearthed. Aside from modifi ed implements such as side-scrapers, splintered and notched pieces, retouched fl akes, hammerstones, tanged pieces and adzes all components of the débitage and differ-ent types of nuclei are present. The manifold material allows in a case study to focus on the analysis of technological aspects in the applied tool production sequences.